The Threat of Information Asymmetries for Supply Chain Management Processes - Frauke KEMPNER (Communications of International Proceedings, 2021)
As part of the corona pandemic, the global networking of economic subjects has created new areas of conflict. Today's supply chain relationships are subject to increased demands that are influenced by a wide variety of stakeholders. This includes not only aspects of sustainability, corporate social responsibility (CSR) and corporate citizenship, but especially the aspect of integrity and information. Although most companies today intend to make supply chains transparent and with integrity in terms of mutual business relationships, various examples in crisis situations reveal the organizations' lack of resilience to harmful or unethical business practices, mainly influenced by information asymmetries. In order to prevent these practices and to protect their own supply chains against attacks from outside, companies must ensure that significant potential dangers are recognized by their partners and eliminated in the second step. The aim of this research work was therefore to use a broad company survey to identify those factors in supply chain management that significantly endanger the integrity of supply chains. For this purpose, a longitudinal survey was carried out, which revealed the authenticity of the partner, the susceptibility of the relationship to interference and the time as essential parameters. On this basis, a resilience strategy for supply chain management is to be developed in further research work.
Keywords: Supply Chain Management; Information asymmetries; Integrity